The detection of wooden foreign bodies: An experimental study comparing direct digital radiography (DDR) and ultrasonography. Issue 4 (November 2018) - Mercado, L.N.S.; Hayre, C.M.
Abstract: Introduction: This experimental study compares the appropriateness of direct digital radiography (DDR) and ultrasonography at detecting soft-tissue wooden foreign bodies (FBs) in extremities. Methods: Varying wooden FB splinters (2 mm, 5 mm and 10 mm) were inserted into eight porcine feet to simulate a patient presenting with a soft-tissue FB injury. Each of the FBs was placed in muscle distant, behind and near bone in the porcine feet. Control groups were used to check for false-positive diagnoses and, based on the presence of FBs; images were given a score depending on the level of visibility by the researcher. Results: A higher detection rate was achieved for all FBs in muscle distant from bone using ultrasound. All of the 2 mm and 5 mm wooden FBs were not detected using DDR. The sensitivity in detecting the FBs was 5.8% and 30% in DDR and ultrasound respectively. Conclusion: Poor sensitivities and specificities were identified in this study. However, this study shows that ultrasound remains superior to DDR at identifying small foreign body objects. This study demonstrates that ultrasound can be a clinically effective tool for detecting suspected wooden FBs >5 mm in the foot and thus should be considered as the primary imaging modality of choice for referring clinicians. Highlights: Utilisation of porcine feet experimentally mimicking human soft tissue. Ultrasonography offers superior detail of wooden foreign bodies. Challenges the utilisation of DDR for wooden FB referrals.